TAp73 and ΔTAp73 isoforms show cell-type specific distributions and alterations in cancer - Vaclav Hrabal; Michaela Stenckova; Filip Zavadil Kokas; Petr Muller; Rudolf Nenutil; Borivoj Vojtesek; Philip J. Coates (Scientific Reports)
Abstract TP73 is a member of the TP53 gene family and produces N- and C-terminal protein isoforms through alternative promoters, alternative translation initiation and alternative splicing. Most notably, p73 protein isoforms may either contain a p53-like transactivation domain (TAp73 isoforms) or lack this domain (ΔTAp73 isoforms) and these variants have opposing or independent functions. To date, there is a lack of well-characterised isoform-specific p73 antibodies. Here, we produced polyclonal and monoclonal antibodies to N-terminal p73 variants and the C-terminal p73α isoform, the most common variant in human tissues. These reagents show that TAp73 is a marker of multiciliated epithelial cells, while ΔTAp73 is a marker of non-proliferative basal/reserve cells in squamous epithelium. We were unable to detect ΔNp73 variant proteins, in keeping with recent data that this is a minor form in human tissues. Most cervical squamous cell carcinomas (79%) express p73α, and the distribution of staining in basal cells correlated with lower tumour grade. TAp73 was found in 17% of these tumours, with a random distribution and no association with clinicopathological features. These data indicate roles for ΔTAp73 in maintaining a non-proliferative state of undifferentiated squamous epithelial cells and for TAp73 in the production of differentiated multiciliated cells.